2020
DOI: 10.1111/sms.13732
|View full text |Cite
|
Sign up to set email alerts
|

Non‐uniform distribution of passive muscle stiffness within hamstring

Abstract: Limited information is available on whether stiffness is different within and between the constituents of the hamstring, that is, the biceps femoris long head (BFlh), semitendinosus (ST), and semimembranosus (SM). Therefore, understanding of hamstring injuries and stretching effect on hamstring stiffness is difficult. The present study primarily aimed to identify whether passive muscle stiffness differs between the BFlh, ST, and SM and between the proximal, middle, and distal sites within each muscle. Secondly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Again, the present study showed, for the first time, significant heterogeneity of BFlh muscle stiffness along its length under active condition (i.e., at 20% MVC), with the distal site being stiffer than the proximal and central sites. The difference may be explained by higher passive muscle stiffness at the distal site within the BFlh 16 . Besides, the site‐specific difference in BFlh muscle stiffness at low contraction intensity may also be explained by spatial variation in EMG activity since BFlh EMG activity at 20% MVC was greater in the distal than the proximal site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Again, the present study showed, for the first time, significant heterogeneity of BFlh muscle stiffness along its length under active condition (i.e., at 20% MVC), with the distal site being stiffer than the proximal and central sites. The difference may be explained by higher passive muscle stiffness at the distal site within the BFlh 16 . Besides, the site‐specific difference in BFlh muscle stiffness at low contraction intensity may also be explained by spatial variation in EMG activity since BFlh EMG activity at 20% MVC was greater in the distal than the proximal site.…”
Section: Discussionmentioning
confidence: 99%
“…Localized shear wave speed (a proxy for stiffness, expressed in the unit of Pascal) was quantified using the ultrasound apparatus in SWE‐mode. According to a previous study that examined the heterogeneous distribution of passive muscle stiffness within the BFlh, 16 the measurement sites of the shear wave speed and EMG activity were determined at the levels of 25% (proximal), 50% (central), and 75% (distal) of the muscle belly length (Figure 2). The optimal probe orientation was adjusted for subject by subject to identify fascicles without interruption across the B‐mode image before data acquisition.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the event of a significant interaction, only comparisons between locations within the same muscle are presented in the Results as these are both clinically and anatomically meaningful. 9,17 Pennation angle for each muscle and location were summarized by means and standard deviations for comparisons with previous investigations. 9,10 Separate Pearson’s correlation coefficients were calculated between the measured pennation angles and extracted SFA parameters values.…”
Section: Methodsmentioning
confidence: 99%
“…Characterization of muscle structure and tissue properties has many important implications in research and clinical care, for example with respect to biomechanical modeling 13,14 or hamstring strain injury risk. 15,16 Recently, studies have investigated regional variation in mechanical properties 17 and activation levels 18 along the hamstrings in response to stretching and various exercises used in injury prevention programs. The role that regional variation of tissue organization of architectural arrangement, tissue properties, and muscle activation may have on factors influencing whole muscle mechanics may have important implications on regions of the hamstring muscles that may be the most susceptible to injury.…”
Section: Introductionmentioning
confidence: 99%